Hatching date variability in wild populations of four coexisting species of African annual fishes - Reichard, Martin; Blažek, Radim; Polačik, Matej; Vrtílek, Milan (Developmental dynamics, 2017)
BACKGROUND: Hatching is modulated by a combination of intrinsic and extrinsic factors. Annual killifish are adapted to complete their entire life cycle in annually desiccating habitats. Spending most of their life in the embryonic stage, they have evolved adaptations to survive desiccated conditions and match their hatching with the unpredictable onset of the aquatic phase of the pool. We examined spatial and temporal synchrony of hatching in natural populations of four species of African annual killifish (genus Nothobranchius). We compared differences and variability in hatching dates among years, regions, pools, and species and matched them with data on inundations of individual pools. RESULTS: Inundations typically coincided with peak rainfall in early January. We found considerable spatial and temporal synchrony in 1 year, but less synchrony in the other 2 years. Hatching generally occurred 0-20 days after inundation; fish at most sites hatched synchronously (<1 week) but some sites showed protracted hatching or two age cohorts. One species tended to hatch earlier than the other three. CONCLUSIONS: We suggest that hatching of annual killifish in the wild is a result of the interplay between environmental conditions and individual predisposition to respond to threshold environmental cues, ensuring effective bet-hedging against unpredictable inundation. Developmental Dynamics 246:827-837, 2017. © 2017 Wiley Periodicals, Inc.
Keywords: životní prostředí; stadia vývoje; fyziologická adaptace; Life Cycle Stages; Environment; Nothobranchius; biologická variabilita populace; Biological Variation, Population; developmental synchrony; Reproduction; Cyprinodontiformes; Animals; diapause; rozmnožování; zvířata; Adaptation, Physiological